Breast Cancer in Men: Public Knowledge and Awareness of Saudi People about its Prevalence and Risk Factors - Khaled, Hayet Ben (Asian Journal of Pharmaceutics (AJP), 2025)
Background: After lung cancer, breast cancer (BC) is the second most prevalent cancer overall and the most common in women. BC can harm men as well, even though it primarily affects women. Aim: The objective of our study is to explore public knowledge regarding BC in men and to assess the knowledge about risk factors of BC and the age at which to begin breast screening. Materials and Methods: A descriptive cross-sectional study was used for 2 months in the Kingdom of Saudi Arabia (KSA). A sample comprised of 502 males and females from different age groups was used. Data were collected by a structured online questionnaire in the Arabic language. After participants filled questionnaire, all data were entered into the Statistical Package for Social Sciences. Results: Of the study group, 53% of participants were female and 47% were male. The majority of the participants (55%) were between the ages of 20 and 30. Of the study group, 27% had a general certificate of secondary education, and 44% had a university degree. About 10% of the study group had a family history of BC, and 49% lived in the Northern border region. 94% of respondents said they knew nothing about male BC or how it is diagnosed. 43% of participants are unaware that BC is influenced by heredity, while 32% believe that from adolescence to age 30, routine BC screening is advised. About 15% believe that gender plays a role in BC risk factors, compared to 8% who believe that genetics plays a role. As a result, women are more knowledgeable than men about BC in men. Conclusion: This study found lack of knowledge and misconceptions regarding male BC and breast screening exist among males and females living in KSA. Public education about BC risk factors, early indications, and diagnosis is needed.